Mô hình hóa trường sóng địa chấn tại bể trầm tích Cửu Long - Tân, Mai Thanh; Viễn, Phan Tiến (Vietnam Journal of Earth Sciences, 2017)
Under the complicated geological conditions in Cuu Long basin, it is important to improve seismicdata processing. The modeling results allow us tounderstand the nature of different types of wavesand then to find the proper processing methods.In this paper, the authors present some seismic modeling results using different methods incomplicated geological environment of Cuu Long basin with the special attention to fractured granite basement. The modeled seismic data will be usedfor selecting optimum processing sequence.The results show that signals received from deepstructures and the fractures within basements areusually very weak and obscured by strong noise level. The presence of high velocity volcanics, high impedance contract surfaces, complicated faulting systemin lower Miocene and Oligocen creates strong noiseand multiples background, which might obscure theseismic signal received from deep layers.Based on the seismic modeling, optimum processes and filters such as -P filter, Radon filters can be selected for enhancing the signal tonoise ratio, and for imaging the signal dispersed inthe fractured basement.